Dampak Sosial Ekonomi COVID-19 di Kawasan Asia Tenggara: Analisis Dinamika dan Strategi Pemulihan - Kartika, Intan Tiara; Adjie, Zulfikar; Adityaningrum, Amanda (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study employs a qualitative method, utilizing data from various books and journals. The research examines the impact of COVID-19 on the GDP of ASEAN countries, which showed economic decline in 2020, along with decreased export and import values, increased unemployment, and rising poverty levels. Interestingly, not all Southeast Asian countries with relatively stable economies during the pandemic managed to curb unemployment rates. In Brunei Darussalam, unemployment remained high despite economic stability. The pandemic also affected economic distribution in complex ways, depending on each country's development level and political stability, as seen in Myanmar. The pandemic's impact on poverty levels in ASEAN countries highlights their structural vulnerabilities. Countries with strong social protection systems, such as Vietnam and Malaysia, mitigated the pandemic's effects on people with low incomes more effectively than those with limited protection, like Cambodia and Myanmar. Additionally, reliance on specific economic sectors, such as tourism and the informal sector, significantly influenced vulnerability to the pandemic's impact. To address these challenges, ASEAN has undertaken various efforts to promote economic recovery through comprehensive approaches, including enhancing intra-regional trade, promoting digital transformation, encouraging sustainable development, and strengthening regional cooperation. These strategies aim not only to recover from the pandemic's immediate impact but also to build a more resilient and integrated ASEAN economy for the future.